Intestinal Absorption of Disodium Monofluorophosphate in the Rat as Affected by Concurrent Administration of Calcium - Beinlich, Axel D.; Brun, Lucas R. M.; Rigalli, Alfredo; Puche, Rodolfo C. (Arzneimittelforschung, 2003)
This paper reports that in the rat coadministration of calcium (calcium chloride, CAS 10043-52-4, Ca2+) enhances intestinal absorption and bioavailability of monofluorophosphate (sodium monofluorophosphate, CAS 10163-15-2, MFP). Evidence obtained with two different experimental models is presented indicating that the latter effects are indirect consequences of the inhibitory effect of Ca2+ on alkaline phosphatase.Pharmacokinetic experiments in previous studies showed that fluorine bound to plasma proteins is the variable that determines the bioavailability of MFP. The area under the curve of fluorine bound to plasma proteins in rats receiving MFP+Ca2+ was significantly greater than in controlsIn isolated duodenal loops in situ, Ca2+ increased the intestinal rate constant of MFP absorption and decreased the rate constant of MFP hydrolysis. Inhibition of hydrolysis increased the concentration of MFP at the intestinal lumen. This fact, however, is not only the cause of increased MFP absorption. Inhibition of alkaline phosphatase with L-phenylalanine, to the same extent as with Ca2+, increased MFP absorption with respect to controls but to a lower degree than with Ca2+. The rate constant of MFP hydrolysis by purified rat intestinal alkaline phosphatase was significantly inhibited by 50 mmol/l Ca 2+ in comparison to control levels. Ca2+ decreased significantly Vmax of the enzyme (p-nitrophenyl phosphate as substrate) and had no effect on Km value. Lineweaver-Burk plots suggested a noncompetitive inhibition mechanism.
Keywords: Calcium; CAS 10043-52-4; CAS 10163-15-2; Monofluorophosphate, bioavailability, pharmacokinetics